2013
DOI: 10.1002/wcs.1226
|View full text |Cite
|
Sign up to set email alerts
|

Embodied cognition

Abstract: Traditional views in philosophy of mind and cognitive science depict the mind as an information processor, one whose connections with the body and the world are of little theoretical importance. On the contrary, mounting empirical evidence shows that bodily states and modality-specific systems for perception and action underlie information processing, and that embodiment contributes to various aspects and effects of mental phenomena. This article will briefly review and discuss some of this evidence and what i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(122 citation statements)
references
References 55 publications
7
88
0
2
Order By: Relevance
“…Thus, the findings support the second hypothesis that the human brain directly couples sensory recognition and motor actions rather than sequentially separating them. Our findings are compatible with alternative frameworks like embodied cognition 8 , sensorimotor contingency 19 , and common coding 13 . However, we also have found roughly as many Motor and Sensory ICs as Sensorimotor ICs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, the findings support the second hypothesis that the human brain directly couples sensory recognition and motor actions rather than sequentially separating them. Our findings are compatible with alternative frameworks like embodied cognition 8 , sensorimotor contingency 19 , and common coding 13 . However, we also have found roughly as many Motor and Sensory ICs as Sensorimotor ICs.…”
Section: Discussionsupporting
confidence: 89%
“…Embodied cognition 8 supports the ideas that perception guides motor actions, motor actions influence perception, and brain concepts are fundamentally grounded in both perception and action 9 . This framework is supported by experimental findings of action intentions influencing visual processing 10 , motor-visual attentional priming 11 , and visuo-motor priming 12 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Notions of embodied cognition (for reviews see Foglia and Wilson 2013;Glenberg et al 2013) formed the final body of scholarship identified by Paas and Sweller (2012) as productive for an evolutionarily informed cognitive load theory. Research has shown that gesturing has a fundamental impact on a range of educationally relevant cognitive functions (for reviews see Goldin-Meadow 2011;Hostetter 2011).…”
Section: An Evolutionarily Informed Cognitive Load Theorymentioning
confidence: 99%
“…Carolan, 2009;Freiler, 2008;Foglia & Wilson, 2013;Macintyre Latta & Buck, 2008). This literature offers a wide range of definitions for 'bodily/body/embodied/ corporeal knowledge'.…”
Section: Introductionmentioning
confidence: 99%